2016
DOI: 10.1016/j.fsigen.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

A molecular exploration of human DNA/RNA co-extracted from the palmar surface of the hands and fingers

Abstract: "Touch DNA" refers to the DNA that is left behind when a person touches or comes into contact with an item. However, the source of touch DNA is still debated and the large variability in DNA yield from casework samples suggests that, besides skin, various body fluids can be transferred through contact. Another important issue concerning touch DNA is the possible occurrence of secondary transfer, but the data published in the literature in relation to the background levels of foreign DNA present on the hand sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 44 publications
3
35
0
1
Order By: Relevance
“…In a survey of samples from handled items, mRNA markers for skin were found in the majority; markers for specific non-skin tissues found in 15% of samples, which had significantly higher DNA yields and less degradation. This suggests that transferred biological material not originating in hands may contribute the highest quality DNA to touch deposits although not necessarily present in most deposits [154]. Although 85% of samples did not display a specific non-skin marker, it does not mean that 85% of touch deposits do not contain exogenous transferred material.…”
Section: Cells Originating Exogenously To the Handsmentioning
confidence: 97%
“…In a survey of samples from handled items, mRNA markers for skin were found in the majority; markers for specific non-skin tissues found in 15% of samples, which had significantly higher DNA yields and less degradation. This suggests that transferred biological material not originating in hands may contribute the highest quality DNA to touch deposits although not necessarily present in most deposits [154]. Although 85% of samples did not display a specific non-skin marker, it does not mean that 85% of touch deposits do not contain exogenous transferred material.…”
Section: Cells Originating Exogenously To the Handsmentioning
confidence: 97%
“…49 One of the simplest of ways to determine the possibility of secondary DNA transfer or background DNA present would be to directly swab an individual's hand which was carried out by Lacerenza et al 120 samples were directly collected from 60 individual's hands where 56 samples had one or more unknown alleles and 36 of those could be classified as mixtures (64.3%). 50 As these DNA samples present in the mixtures were foreign to that of the volunteer, it could be concluded that either secondary DNA transfer occurred or that these profiles were a part of the background DNA present on that individual's hand. 50 A new substrate was then used by van den Berge et al where individuals dragged each other mimicking an activity-related scenario.…”
Section: Indirect Findings Of Secondary Transfermentioning
confidence: 99%
“…50 As these DNA samples present in the mixtures were foreign to that of the volunteer, it could be concluded that either secondary DNA transfer occurred or that these profiles were a part of the background DNA present on that individual's hand. 50 A new substrate was then used by van den Berge et al where individuals dragged each other mimicking an activity-related scenario. Samples were taken from the knee-area of the trousers where the dragger did not touch resulting in 26 samples, 3 of which did not result in over 7 alleles.…”
Section: Indirect Findings Of Secondary Transfermentioning
confidence: 99%
“…Other studies examining the transfer of "touch" DNA in less controlled scenarios, considered more realistic examples of secondary transfer rates, have observed the transferred DNA as the major or only component to the profile on far fewer occasions, if at all:~2.8% in studies where the source of the transferred DNA was known (9-12);~1.4% in studies where the source of the transferred DNA was unknown (13,14). Several other studies allude to the detection of secondarily transferred DNA from known and/or unknown sources within the samples obtained, but provide insufficient information with respect to their presence forming a minor or major component of the profile, and in the case of foreign alleles, whether they originated from a single or multiple sources (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Sirmentioning
confidence: 99%
“…Studies have provided empirical evidence of secondary (and further, including tertiary and quaternary) transfer (9,10,16,27), have investigated variables that may affect the transfer and subsequent detection of touch DNA (7,8,13,18,20,(22)(23)(24)28,29), have provided casework relevant examples and simulations to model the possible effect of transfer on conclusions (9)(10)(11)14,16,17,21,(30)(31)(32), and have provided statistical models to evaluate the possibility of transfer (33)(34)(35). Such studies have been conducted with various autosomal STR methods employed in forensic biology, including the current sensitive technologies, and, more recently, with alternate methods such as mRNA profiling (18,21). While the articles cited above refer only to the transfer of "touch" DNA, the authors would like to acknowledge that there are numerous other studies investigating the transfer of other biological fluids not cited here that also contribute to our general knowledge of DNA transfer within the forensic context.…”
Section: Sirmentioning
confidence: 99%